Acclimatization: The Schomburgk brothers in South Australia - Weigl, Engelhard (HiN – Alejandro de Humboldt en la Red. Revista internacional de estudios humboldtianos, 2003)
Abstract Together with their wives Otto and Richard Schomburgk arrived in Port Adelaide (South Australia) on August 16th 1849. The essay looks at how these two brothers, who had received their scientific training and promotion in the circle surrounding Alexander von Humboldt, reacted to the unfamiliar conditions in the young British colony. Some indication will be given as to the differences between the Schomburgk brothers treatment of the natural resources of the new colony and that of the English colonists of the time. Zusammenfassung Otto und Richard Schomburgk erreichten zusammen mit ihren Frauen Port Adelaide (Südaustralien) am 6. August 1849. Der Beitrag geht der Frage nach, wie die Brüder, die ihre wissenschaftliche Ausbildung und Förderung im Umkreis von Alexander von Humboldt erhalten haben, auf die unbekannten klimatischen Bedingungen in der noch jungen englischen Kolonie reagierten. Dabei soll die Differenz der Schomburgk Brüder zu den englischen Kolonisten im Umgang mit den Ressourcen der neuen Kolonie sichtbar werden.